x^2+bx+c=0 x1+x2=b x1*x2=-c x1=2; x2=-8 2-8=-6 2*8=16; -(+16)=-16 x^2+6x-16=0 Подставляем и все правильно, значит ответ x^2+6x-16=0
x^2+bx+c=0 x1+x2=-b x1+x2=c x1=0,1; x2=3 3+0,1=3,1; -(+3,1)=-3,1 3*0,1=0,3 x^2-3,1x+0,3=0 Подставляем и все верно, значит ответ x^2-3,1x+0,3=0 ВСЕ БЫЛО СДЕЛАНО ПО ТЕОРЕМЕ ВИЕТА.
Answers & Comments
x^2+bx+c=0
x1+x2=b
x1*x2=-c
x1=2; x2=-8
2-8=-6
2*8=16; -(+16)=-16
x^2+6x-16=0
Подставляем и все правильно, значит ответ x^2+6x-16=0
x^2+bx+c=0
x1+x2=-b
x1+x2=c
x1=0,1; x2=3
3+0,1=3,1; -(+3,1)=-3,1
3*0,1=0,3
x^2-3,1x+0,3=0
Подставляем и все верно, значит ответ x^2-3,1x+0,3=0
ВСЕ БЫЛО СДЕЛАНО ПО ТЕОРЕМЕ ВИЕТА.